Anaesthesia use in catheter ablation for atrial fibrillation: a systematic review and meta-analysis of observational studies. Issue 2 (14th August 2019) - Li, Ka Hou Christien; Sang, Tian; Chan, Cheng; Gong, Mengqi; Liu, Yingzhi; Jesuthasan, Aaron; Li, Guangping; Liu, Tong; Lam, Michael H S; Wu, William KK; Chan, Matthew T V; Liu, Fang-zhou; et al.
Abstract : Objectives: This meta-analysis and systematic review seeks to compare both characteristic parameters and procedural outcomes of atrial fibrillation (AF) catheter ablation in patients under general anaesthesia (GA)/deep sedation and mild/moderate sedation. Background: Catheter ablation has become a widely applied intervention for treating symptomatic AF and arrhythmias that are refractory to medical therapy. It can be conducted through from mild sedation to GA. Methods: PubMed and Embase were searched up to July 2018 for randomised controlled trials, cohort and observational studies that assessed the outcomes of catheter ablation under GA/deep sedation or mild/moderate sedation. Nine studies were included in this meta-analysis after screening with the inclusion and exclusion criteria. Heterogeneity between studies and publication bias was evaluated by I 2 index and Egger's regression, respectively. Results: Our meta-analysis found catheter AF ablation with GA/deep sedation to be associated with reduced risk of recurrence (RR: 0.79, 95% CI 0.56 to 1.13, p=0.20) and complications (RR: 0.95, 95% CI 0.64 to 1.42, p=0.82), though statistically insignificant. In terms of procedural parameters, there was no significant difference between the two groups for both procedural time (SMD: −0.13, 95% CI −0.90 to 0.63, p=0.74) and fluoroscopy time (SMD: −0.41, 95% CI −1.40 to 0.58, p=0.41). Univariate meta-regression did not reveal any covariates as a moderating factor for complication and recurrence risk. Conclusion: Apart from an increased likelihood of procedural success, ablation by GA/deep sedation was found to be non-significantly different from the mild/moderate sedation approach in both procedural parameters and outcome measures.